Analysis Of Various Pwm Schemes For The Design Of Asymmetric Single Phase 31 Level Cascaded Mli - S. Siva Prasad, D.Lakshmi,G.Ezhilarasi, S.Baskaran (International Journal of Advanced Science and Technology, 2020)
Multilevel inverter is most fashionable due to bargain switching losses, low costs, minimum harmonic distortion and high voltage capacity while compared with conventional PWM converters. A latest family of multilevel inverters that are emerged with less number of isolated DC input sources is asymmetric multilevel inverter. This work comprises of design and analysis of various PWM modulation schemes available for thirty one level asymmetric multilevel inverters. The relative case study is offered to authenticate the tested modulation scheme through harmonic spectrum analysis, total harmonic distortion (THD), and distortion factor (DF). The chosen single phase ternary DC source based multilevel inverter is demonstrated via MATLAB simulation. Finally the experimental result shows that APOD PWM offers relatively distortion-less AC output. It is also realized that the COPWM strategy output waveforms as it delivers fundamental rms AC output voltage with high magnitude.